2015
DOI: 10.1371/journal.pone.0131270
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Role of Inversion Polymorphism of Drosophila subobscura in Lead Stressed Environment

Abstract: Local adaptation to environmental stress at different levels of genetic polymorphism in various plants and animals has been documented through evolution of heavy metal tolerance. We used samples of Drosophila subobscura populations from two differently polluted environments to analyze the change of chromosomal inversion polymorphism as genetic marker during laboratory exposure to lead. Exposure to environmental contamination can affect the genetic content within a particular inversion and produce targets for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Further, different populations of organisms often respond differently to metal toxicity due to adaptations to their local environment. For example, populations sampled near a nickel mine may show fewer toxic effects following Ni exposure than populations sampled from relatively clean environments [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, different populations of organisms often respond differently to metal toxicity due to adaptations to their local environment. For example, populations sampled near a nickel mine may show fewer toxic effects following Ni exposure than populations sampled from relatively clean environments [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Segregating chromosomal inversions are present in fungi ( Perkins 1997 ; Ohm et al 2012 ) and are widespread in higher eukaryotes such as plants ( Lowry and Willis 2010 ), snails ( Johannesson and Mikhailova 2003 ), fruit flies ( Feder et al 2003 ), rodents ( Wise and Pravtcheva 2004 ), and humans ( Stefansson et al 2005 ; Zody et al 2008 ; Donnelly et al 2010 ; Ma and Amos 2012 ; Salm et al 2012 ). They are known to be involved in local adaptation of various species such as Drosophila melanogaster ( Brehm and Krimbas 1991 ; Munte et al 2005 ; Zivanovic et al 2014 ; Kenig et al 2015 ) and Anopheles ( Coluzzi et al 2002 ). The process of local adaptation is environment specific and different genes are favored in different environments.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been found that upon reversion to standard nutrition, flies whose prior generations have been exposed to a high-protein diet displayed multigenerational inheritance of altered gene expression [38]. Moreover, populations of Drosophila subobscura retain signatures from past contamination events with heavy metals [39], while exposure to G418 stress reduces the maternal levels of polycomb in the offspring embryos; this reduction contributed to the inheritance of induced gene expression patterns [40].…”
Section: Discussionmentioning
confidence: 99%